2015
DOI: 10.3109/13880209.2014.1003354
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential of lichen species and their secondary metabolites. A systematic review

Abstract: Context: Pharmacological interest of lichens lies in their capacity to produce bioactive secondary metabolites, being most of them phenolic compounds with reactive hydroxyl groups that confer antioxidant potential through various mechanisms. Increasing incidence and impact of oxidative stress-related diseases (i.e., neurodegenerative disorders) has encouraged the search of new pharmacological strategies to face them. Lichens appear to be a promising source of phenolic compounds in the discovery of natural prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
83
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 84 publications
4
83
0
1
Order By: Relevance
“…Ample data exist to prove lichens as a reliable source of antioxidants. There are already several reviews on antioxidant activities of lichen extracts and their compounds [25, 26]. Reviewing the antioxidant activities of lichen compounds is beyond the scope of this study.…”
Section: Antioxidant Activities Of Lichen Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ample data exist to prove lichens as a reliable source of antioxidants. There are already several reviews on antioxidant activities of lichen extracts and their compounds [25, 26]. Reviewing the antioxidant activities of lichen compounds is beyond the scope of this study.…”
Section: Antioxidant Activities Of Lichen Compoundsmentioning
confidence: 99%
“…Adequate literature exists, for certain lichens to be a viable source of antioxidants [9, 10, 24, 25]. Their antioxidant potential has been assessed in a number of assays, including, DPPH radical scavenging, reducing power, superoxide anion radical scavenging, nitric oxide radical scavenging, and lipid peroxidation inhibition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lichens are symbiotic association between a mycobiont (fungus) and either algae or cyanobacterium [27][28][29]. Besides lichens species are able to produce important secondary metabolites [30].…”
Section: Lichens As Antioxidants and Tau Inhibitors Sourcementioning
confidence: 99%
“…Various scientific reports suggested that lichens present antimicrobial, antiprotozoal, anti-inflammatory, antipyretic, and antiproliferative (antitumor) activities [1113]. Regarding their antioxidant potential, it could be considered that lichens are poorly known when compared to higher plants or other fungus, despite recent investigations are dealing with the issue; only a few lichens species and compounds have exerted promising antioxidative potentials (as reviewed in Fernández-Moriano et al [14]) and further studies are encouraged to deeply understand the value of lichen compounds as protective antioxidant agents.…”
Section: Introductionmentioning
confidence: 99%